Revit: Parametric Curvature in the Family Editor. - F. Aubin, Paul (linkedin.com, 2018)
Tame unruly parametric curves. Learn how to control the curvature of nonrectilinear geometry such as circles, arcs, arches, splines, and complex curves like cyma moldings.